Quantum Boolean algebras - Diaz, R. (Algebra and Discrete Mathematics, 2017)
We introduce quantum Boolean algebras which are the analogue of the Weyl algebras for Boolean affine spaces. We study quantum Boolean algebras from the logical and the set theoretical viewpoints.